Carbonation-induced volume change in alkali-activated slag. (30th July 2017) - Ye, Hailong; Radlińska, Aleksandra
Highlights: Crystal growth model explains the carbonation-induced volume change in AAS. The effect of different types of cation and anion in activator on AAS is studied. New insights on the mechanisms of volumetric instability of AAS are provided. Abstract: In this work, the volume changes of alkali-activated slag (AAS) paste prepared using various types of activator were characterized at nitrogen and atmospheric conditions. The results show that atmospheric carbonation of AAS results in volumetric expansion and disintegration, which may be attributed to the generation of crystallization stress in restrained pore spaces. This study suggests that the carbonation-induced volume change in cementitious materials is a combined result of chemical reactions and physical characteristics, depending on hydrated phase assemblage, composition, and pore structure of cementitious solids. The potassium ions (K + ), compared to sodium ions (Na + ), can enter the interlayer space of calcium-alumina-silicate-hydrate (C-A-S-H), distort the C-A-S-H layers stacking, coarsen the pore structure, and make AAS more vulnerable to carbonation. It is suggested that the high alkali content in AAS systems contributes considerably to its poor volumetric stability under carbonation.